(3TQM eNJUQ efJgi GdhUhd hGdCed aj Ydei GdCUhd hGdLOds - (3CHh GdbGSe eMeO Hf eSYhO GdTjQGRis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3hHYO aEf eYGTQ ENhGfi ai GdOjf edJeSjf Cf CTQM dge eNJUQ efJgi GdhUhd hGdCed ai Ydei GdhUhd hGdLOd GdPi UfYg GHf GdMGLH s
(3BNQgG (B:s
(3dYOe ESJdRGeg dg hYdi JbOjQ GdJSGhi jSde eG PcQfGg ChdkG ced GdSaQ GdChd ef TQM GdTjQGRi Ydi eNJUQ efJgi GdhUhd CHj YeQh Hf GdMGLH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1625 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1853s
Keywords: (3GdJhMjO hGdedd hGdfMds